The Solidarity Contribution in the Light of Municipal Autonomy in the Jurisprudence of the Hungarian Constitutional Court - Ráth Olivér Zoltán; Varga Ádám (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2025)
In Hungary, the so-called solidarity contribution has been part of the annual central budget act since 2017, representing a payment obligation for local self-governments to the central state budget. Some argue that the solidarity contribution, which is based on local business tax capacity per inhabitant, is nothing more than a central tax on municipalities with high tax capacity. In its original form, the solidarity contribution affected only a small percentage of municipalities in 2017. However, as a result of annual changes to the rules, the number of municipalities paying solidarity contributions has increased almost fivefold ( from 166 in 2017 to 855 in 2025), meaning that approximately one in four municipalities will pay solidarity contributions in 2025. Similarly, over the past nine years, the planned revenue from the solidarity contribution has increased almost eighteenfold ( from 21 billion HUF to 360 billion HUF). This study examines the evolution of the solidarity contribution in relation to the financial autonomy of local self-governments, considering the decisions of the Constitutional Court regarding infringements of the European Charter of Local Self-Government.